Landscape design and neighbourhood green spaces as urban wildlife habitats in the Klang Valley, Peninsular Malaysia / Nik Hanita Nik Mohamad - Nik Mohamad, Nik Hanita (2010)
Rapid urbanisation in Malaysia has resulted in the loss and fragmentation of lowland tropical forests. Due to the modification of habitat needs provided by these natural green spaces, the diversity and population of urban wildlife have significantly reduced. The urban parks provided are recognised as an effective urban conservation strategy to mitigate the effects of urbanisation by conserving, enhancing and creating new habitats for urban wildlife. Despite this, the potential of neighbourhood green spaces to function as urban wildlife habitats has never been optimised. Similarly, landscape ecology principles that have been recognised to guide in the successful implementation of wildlife habitat designs are seldom adopted in design efforts in Malaysia. This thesis addresses the issue of sustainable communities by integrating sociological, ecological and design dimensions. It examines the ecological approaches adopted by a group of landscape architects in their design of neighbourhood green spaces that have successfully culminated in the conservation, enhancement, and/or creation of wildlife habitats. In addition, the attitudes of housing residents in the Klang Valley toward urban wildlife and habitats were also examined. The research, therefore, has sought to investigate through a combination of surveys, case studies, interviews and observations on landscape architects and residents in the Klang Valley.